MicroRNAs Differentially Expressed in Actinic Keratosis and Healthy Skin Scrapings - Maria Vincenza Chiantore; Marco Iuliano; Roberta Maria Mongiovì; Fabiola Luzi; Giorgio Mangino; Lorenzo Grimaldi; Luisa Accardi; Gianna Fiorucci; Giovanna Romeo; Paola Di Bonito (Biomedicines, 2023)
Actinic keratosis (AK) is a carcinoma in situ precursor of cutaneous squamous cell carcinoma (cSCC), the second most common cancer affecting the Caucasian population. AK is frequently present in the sun-exposed skin of the elderly population, UV radiation being the main cause of this cancer, and other risk factors contributing to AK incidence. The dysregulation of microRNAs (miRNAs) observed in different cancers leads to an improper expression of miRNA targets involved in several cellular pathways. The TaqMan Array Human MicroRNA Card assay for miRNA expression profiling was performed in pooled AK compared to healthy skin scraping samples from the same patients. Forty-three miRNAs were modulated in the AK samples. The expression of miR-19b (p < 0.05), -31, -34a (p < 0.001), -126, -146a (p < 0.01), -193b, and -222 (p < 0.05) was validated by RT-qPCR. The MirPath tool was used for MiRNA target prediction and enriched pathways. The top DIANA-mirPath pathways regulated by the targets of the 43 miRNAs are TGF-beta signaling, Proteoglycans in cancer, Pathways in cancer, and Adherens junction (7.30 × 10−10 < p < 1.84 × 10−8). Selected genes regulating the KEGG pathways, i.e., TP53, MDM2, CDKN1A, CDK6, and CCND1, were analyzed. MiRNAs modulated in AK regulate different pathways involved in tumorigenesis, indicating miRNA regulation as a critical step in keratinocyte cancer.